"Beyond words": a researcher's guide to using photo elicitation in psychology. Issue 4 (2nd October 2017) - Bates, Elizabeth A.; McCann, Joseph J.; Kaye, Linda K.; Taylor, Julie C.
ABSTRACT: The use of photo elicitation is limited within the field of psychology despite its theoretical and practical potential. It offers significant benefits as a qualitative method that could present a new and interesting way of exploring previously understood topics within the discipline. Within our discussion, we present a step-by-step guide outlining the key practical stages and ethical assurances involved in photo elicitation research, using our ongoing research as an illustrative example. It is intended that this could be used as a model of good practice for developing research paradigms beyond those typically used within the psychology discipline.